2007
DOI: 10.1055/s-2005-919109
|View full text |Cite
|
Sign up to set email alerts
|

Gewichtsveränderungen unter Therapie mit Psychopharmaka

Abstract: Beside some methodological restrictions like inconsistent information of weight changes (e. g. percent vs. mass) and the small sample of available long term studies, this review specifies the incidence of weight changes for commonly used psychotropic drugs and might be helpful to look for alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…However, case reports are limited by the presence of unadjusted confounders and it is therefore hard to draw any causal inference from this. In a larger study, Drieling, Biedermann, Schärer, Strobl & Langosch (2007) reported that SSRIs did not significantly interfere with weight or height. So far, little evidence supports the notion that potential short stature among OCD patients is due to SSRI use, or that there is a specific medication by gender interaction effect on height.…”
Section: Discussionmentioning
confidence: 96%
“…However, case reports are limited by the presence of unadjusted confounders and it is therefore hard to draw any causal inference from this. In a larger study, Drieling, Biedermann, Schärer, Strobl & Langosch (2007) reported that SSRIs did not significantly interfere with weight or height. So far, little evidence supports the notion that potential short stature among OCD patients is due to SSRI use, or that there is a specific medication by gender interaction effect on height.…”
Section: Discussionmentioning
confidence: 96%
“…Estimates range from little to no weight gain to 8 kg or more within the first 3 to 6 months, with younger patients and those with a lower pretreatment body mass index being at highest risk. Comparison of specific medications indicate a higher risk with clozapine and olanzapine, while aripiprazole and ziprasidone may be weight neutral or cause lesser amounts of weight gain (47)(48)(49).…”
Section: Medication Side Effectsmentioning
confidence: 99%
“…Adipositas betroffen. Neben von Medikamenten unabhängigen Faktoren wie verminderte körperliche Aktivität, Fehlernährung, Substanzabhängigkeit oder Depression kommt der Gewichtszunahme durch Psychopharmaka eine besondere Bedeutung zu (1)(2)(3). Gewichtszunahme führt zu einem erhöhten Risiko für kardiovaskuläre Erkrankungen.…”
unclassified